Characteristics of Shiga toxin producing- and enteropathogenic Escherichia coli of the emerging serotype O80:H2 isolated from humans and diarrhoeic calves in Belgium. (January 2019) - De Rauw, K.; Thiry, D.; Caljon, B.; Saulmont, M.; Mainil, J.; Piérard, D.
Abstract: Objectives: Recently a highly virulent Escherichia coli O80:H2 pathotype carrying Shiga toxin genes, the intimin subtype eaeξ, and genes associated with the extraintestinal pathogenic E. coli (ExPEC) pS88 plasmid was described in France. In this study we examine the relatedness of Belgian E. coli O80:H2 isolated from humans and diarrhoeic calves as well their similarities with the French pathotype. Methods: Eighteen Belgian E. coli O80:H2 strains (nine human Shiga toxin-producing E. coli (STEC) (2008–2016), two bovine STEC (1987) and seven bovine atypical enteropathogenic E. coli (aEPEC) (2009–2015)) were characterized with conventional PCR, disc diffusion susceptibility testing and whole genome sequencing. Results: Only nine sporadic human STEC O80:H2 cases have been detected in Belgium. All patients were female, just two of them suffered from haemolytic uremic syndrome. All studied strains had the eaeξ subtype, belonged to the multi-locus sequence type ST-301, and carried virulence genes associated with the type III secretion system and effectors not encoded by the locus of enterocyte effacement (LEE). Multiple genes of the pS88 plasmid were detected in all but two strains (one human and one calf STEC). The Shiga toxin subtypes stx1a ( n  = 3; one human, two calf), stx2a ( n  = 2) and stx2d ( n  = 6) were detected. All strains were multidrug resistant, two were extended-spectrum β-lactamase positive. Core genome MLST revealed that some human and calf E. coli differed by only 22 loci. Conclusions: The STEC/ExPEC O80:H2 pathotype was present in calves in Belgium as early as 1987, but human infections have been rare and mostly mild. The human STEC and bovine aEPEC cluster together and have the potential to be as virulent as the French isolates, as shown by their similar gene content.